Exploring the Potential of Chatbots: Insights into Consumer Preferences for Chatbots and Chatbot Interaction Content - Johar, Chetna (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2024)
The proliferation of chatbots has revolutionised customer service. By simulating human-human interaction and real-time information dissemination, chatbots enhance customer experiences while saving costs for businesses. However, despite their benefits, chatbot adoption remains limited due to user scepticism. Through a series of three studies, this PhD research aims to understand perceptions of chatbots and explores conversation styles that can mitigate negative perceptions and enhance customer experiences. Study 1 examines users' intentions to contact customer service through chatbots in comparison to alternative modes of contact. The findings reveal that consumers do not consistently exhibit positive intent for using chatbots throughout their customer journey, prompting an exploration of methods to enhance customer satisfaction in chatbot interactions. Thus, studies 2 and 3 demonstrate that chatbots utilising social interaction content (versus functional interaction content) are perceived as more empathetic by consumers, leading to increased customer satisfaction. However, two factors moderate this effect: 1) the disclosure (vs. non-disclosure) of the chatbot's identity, and 2) the successful (vs. non-successful) service outcome of the service provided by the chatbot. In cases where chatbots fail to provide the required service, chatbots utilising functional interaction content (versus social interaction content) are perceived as more competent, resulting in increased customer satisfaction. This research is the first to explore consumer perceptions of chatbots in comparison to other modes of contact across various customer journey touchpoints. Additionally, it contributes to the existing knowledge on types of interaction content for enhancing customer experiences. This research also holds significant managerial implications as it enables companies to tailor chatbot strategies based on user intentions throughout the customer journey and implement suitable conversation styles to enhance customer experiences, thereby increasing chatbot adoption rates and improving overall customer satisfaction.
APPROVED
Keywords: Customer experience; Interaction content; Chatbot Identity Disclosure; Chatbot service failure; Perceived empathy; Perceived competence; Chatbots